Political Metaphors and the Reputational Image of Power: Experience in Classifying Sociological Survey Data - L. V. Nikiforova; N. N. Rozanova (Научный диалог, 2022)
The questions of classification of political metaphors are considered. This classification is necessary for the analysis of the data of sociological survey, which was conducted by the team of Smolensk University in 2022 in regions of Russia. The study of the reputational image of power (respondents' answers to the questions: “How would you draw the reputational image of Russian / regional power?”) problematizes the principles of classification. The relevance of the study in working out the diagnosis of the reputational image of power. The novelty of the study is that the analysis was conducted on the basis of folk metaphorization, rather than professional political discourse, which researchers of political metaphorology and political semantics usually deal with. The empirical material for the problematization of the classification was the results of the sociological survey 2021, which included similar questions. The classification of power metaphors on the basis of major philosophical categories and structural relationships (space/time; living/artificial; human/nature/society) is presented, as such principle allows capturing the real diversity and multidimensionality of figurative likenesses proposed by respondents. The results of the study of folk metaphorization adjust the existing classifications of power metaphors, do not fully coincide with the known classifications of metaphorical models of power, also adjust the ideas about the popularity of typical metaphorical models.